2017
DOI: 10.1111/gcb.13723
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of seasonal leaf area index trends in the northern latitudes with “optimally” integrated ecosystem models

Abstract: Significant increases in remotely sensed vegetation indices in the northern latitudes since the 1980s have been detected and attributed at annual and growing season scales. However, we presently lack a systematic understanding of how vegetation responds to asymmetric seasonal environmental changes. In this study, we first investigated trends in the seasonal mean leaf area index (LAI) at northern latitudes (north of 30°N) between 1982 and 2009 using three remotely sensed long-term LAI data sets. The most signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 86 publications
2
53
0
Order By: Relevance
“…Zhu, Z. et al [66] used ten ecosystem models and suggested that the positive trends during summer, autumn and spring in the Northern latitudes (> 30 • N) are mainly due to elevating atmospheric CO 2 concentration. The effects of nitrogen deposition and land use change would be relatively small.…”
Section: Northern Mid and High Latitudesmentioning
confidence: 99%
“…Zhu, Z. et al [66] used ten ecosystem models and suggested that the positive trends during summer, autumn and spring in the Northern latitudes (> 30 • N) are mainly due to elevating atmospheric CO 2 concentration. The effects of nitrogen deposition and land use change would be relatively small.…”
Section: Northern Mid and High Latitudesmentioning
confidence: 99%
“…There are large model‐to‐model differences in both the direction and magnitude of the effects induced by climate forcing and land‐use change. Furthermore, the trends in GPP driven by climate forcing, atmospheric CO 2 , land‐use change and nitrogen deposition were computed by using segmented linear regression breaking at the sixtieth (Zhu et al, ). The model factorial simulations suggested that the dominant environmental drivers were consistent during 1901–2010 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…are often used to evaluate the models. However, a relatively large discrepancy among these long-term LAI products has also been reported in some recent studies (Xiao et al, 2017;Zhu et al, 2017). Therefore, the uncertainty of LAI data itself should be considered when evaluating model performances.…”
Section: 1029/2018gb005909mentioning
confidence: 96%
“…In addition, large discrepancies between models were found when predicting ecosystem variability and trends Zhu et al, 2017). Unsurprisingly, the dominant factors obtained from different models are often significantly different (Beer et al, 2010;Huntzinger et al, 2017).…”
Section: Intercomparison Project Phase 5 (Cmip5) Reported That Most Dmentioning
confidence: 99%
“…Ichii et al, 2013;Piao et al, 2013;Zhang et al, 2015). However, performance in predicting LAI and GPP trends and variability has been found to vary among models (Murray-Tortarolo et al, 2013;Piao et al, 2013;Anav et al, 2015;Zhu et al, 2017). To better assess model performance in this regard, we selected 13 sub-regions associated with 5 different regional climate and land cover conditions ( Table 1) This improvement may be due to SSiB4/TRIFFID better capturing the interannual variability in semi-arid areas which dominate interannual variability (Ahlstrom et al, 2015).…”
Section: Assessment Of the Simulated Vegetation Temporal Variabilitymentioning
confidence: 99%